Outcomes of fenestrated-branched endovascular aortic repair of thoracoabdominal aortic aneurysms in patients with heritable thoracic aortic diseasesCentral MessagePerspective - Lucas Ribé, MD; Lucas Ruiter Kanamori, MD; Bruno P. Schmid, MD; Thanila A. Macedo, MD; Bernardo C. Mendes, MD; Steven Maximus, MD; Ying Huang, MD, PhD; Felipe Nasser, MD, PhD; Gustavo S. Oderich, MD (JTCVS Techniques)
Objective: Open surgical repair is the first-line treatment for patients with complex aortic aneurysms and heritable thoracic aortic diseases (HTADs). Fenestrated-branched endovascular aortic repair (FB-EVAR) has been used selectively in higher-risk patients. This study assessed early- and midterm outcomes of FB-EVAR for complex aortic aneurysms in patients with HTADs. Methods: We reviewed clinical data, imaging, and outcomes of consecutive patients treated by FB-EVAR for complex abdominal and thoracoabdominal aneurysms from April 2007 to June 2024. Patients with confirmed Marfan syndrome, Loeys-Dietz syndrome, vascular Ehlers-Danlos syndrome, or ACTA2 mutation were included. End points included 30-day mortality and major adverse events, cumulative incidence of aortic-related mortality, aortic aneurysm rupture, and secondary interventions. Results: Among 850 patients (median age, 58 years; interquartile range, 49-70 years; 8 [53%] men) treated by FB-EVAR for complex abdominal aortic aneurysms and thoracoabdominal aortic aneurysms, 15 (1.8%) had confirmed HTADs. Technical success was achieved with no early mortality in all patients. Early outcomes showed no cerebrovascular or major cardiac events. One patient developed delayed paraparesis with complete recovery. Median follow-up was 20 months (interquartile range, 13-34 months) with no aortic-related mortality and aortic aneurysm rupture. One patient developed a late retrograde dissection treated by thoracic endovascular aortic repair. Patient survival and cumulative incidence of secondary interventions at 1 year were 93% ± 16% and 10.0% (95% CI, 0.0%-26.8%), respectively. Conclusions: FB-EVAR in select patients with a confirmed diagnosis of HTADs was associated with high technical success and no early mortality. Midterm outcomes revealed no aortic-related mortality or aortic aneurysm rupture, but 1 in 3 patients required secondary interventions, highlighting the importance of continuous surveillance in this population.